2021
DOI: 10.1016/j.ekir.2021.02.034
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of Hypertensive Kidney Donors Using Current and Past Hypertension Definitions

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 27 publications
1
9
0
Order By: Relevance
“…Some uncertainty exists when applying these risk estimates to current donor candidates, because in the present era there is less cardiovascular disease and more diabetes. Nevertheless, the strength of association between hypertension and cardiovascular outcomes reported by Ibrahim et al 6 is of a similar magnitude as found in the general population. 7 In their conclusion, Ibrahim et al 6 focus on the lack of increased risk of ESKF and advocate for allowing hypertensive persons to donate if subtle renal disease is ruled out and the candidate is not at a magnified risk of cardiovascular disease from other risk factors than hypertension.…”
Section: See Clinical Research On Page 1242supporting
confidence: 76%
See 2 more Smart Citations
“…Some uncertainty exists when applying these risk estimates to current donor candidates, because in the present era there is less cardiovascular disease and more diabetes. Nevertheless, the strength of association between hypertension and cardiovascular outcomes reported by Ibrahim et al 6 is of a similar magnitude as found in the general population. 7 In their conclusion, Ibrahim et al 6 focus on the lack of increased risk of ESKF and advocate for allowing hypertensive persons to donate if subtle renal disease is ruled out and the candidate is not at a magnified risk of cardiovascular disease from other risk factors than hypertension.…”
Section: See Clinical Research On Page 1242supporting
confidence: 76%
“…This is different in a 30-year-old potential donor, in which isolated hypertension is both rare and strongly indicative of future health problems, whether related to hereditary factors or lifestyle. Although Ibrahim et al 6 do not make a clear stand on age limits for potential donors with hypertension, they suggest that a limit of 50 years of age may be reasonable. We support the concept of such a lower age limit for considering hypertensive donors.…”
Section: See Clinical Research On Page 1242mentioning
confidence: 98%
See 1 more Smart Citation
“…Our results indicate that at the period of live renal donation the HTNin spite of using of anti HTN medications, after the donation the new-onset CRF is a long-term cause considered as risk.For the duration offollow up for about 8.0 year 38.4% of the subject having an eGFR of less than 60 ml because of the retrospective sample style, these figures should be taken with caution, but these between series of incidence of 37% within 8 years of donating kidney 9 . Six of the 50 donors (3%) had an eGFR of 46mL after a mean period of follow-up of 4.8 -2.3 years, but not found in matched other stable non-donors eGFR of less than 60 mL after live kidneydonation on health outcomes is up till now a hot topic for debate.…”
Section: Discussionmentioning
confidence: 99%
“…A recent analysis, however, demonstrated that a third of kidney donors developed hypertension 15 years after donation compared to <10% in nondonor healthy controls [4]. We have recently shown that hypertension development in kidney donors is associated with older age, male gender, a higher body mass index (BMI), and a higher fasting plasma glucose [5]. Importantly, hypertension at donation was not associated with an increased risk of kidney failure [5].…”
Section: Introductionmentioning
confidence: 99%